Do outliers and unobserved heterogeneity explain the exporter productivity premium? Evidence from France, Germany and the United Kingdom - Yama Temouri; Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
A stylized fact from the literature on the Micro-econometrics of International Trade and a central implication of the heterogeneous firm models from the New New Trade Theory is that exporters are more productive than non-exporters. It is argued that this exporter productivity premium is due to extra costs of exporting that can be covered only by more productive firms. However, in recent papers that control for extreme observations and unobserved firm heterogeneity by applying a highly robust fixed-effects estimator, no such exporter productivity premium is found for firms from manufacturing and services industries in Germany. This paper uses enterprise level panel data for France, Germany and the United Kingdom from 2003 to 2008 to systematically investigate the role of outliers and unobserved firm heterogeneity for estimates of the exporter productivity premium. We report that outliers do have an influence on the estimated exporter productivity premium. We argue that the vanishing exporter premium in robust fixed effects estimations that is reported for all three countries is caused by characteristics of firms that start or stop to export over the period under investigation, and that are not representative for the bulk of firms that either export or not.
Keywords: F14; 330; Export; productivity premium; outlier; unobserved heterogeneity; robust estimation